2015
DOI: 10.1128/aac.04955-14
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Pharmacokinetic-Pharmacodynamic Relationships for Fosfomycin Efficacy Using an In Vitro Infection Model

Abstract: c Fosfomycin, a phosphonic class antibiotic with a broad spectrum of antibacterial activity, has been used outside the United States since the early 1970s for the treatment of a variety of infections. In the United States, an oral (tromethamine salt) formulation is used for uncomplicated urinary tract infections. Recently, there has been interest in the use of an intravenous solution (ZTI-01) for the treatment of a broad range of infections associated with multidrug-resistant bacteria. In this era of multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…As there is interest in use of parenteral fosfomycin for treatment of indications in addition to uncomplicated UTI, recent hollow fiber pharmacokinetic/pharmacodynamic (PK/PD) studies were undertaken by the Ambrose group (VanScoy et al 2015) to determine the PK/PD index for IV fosfomycin and to determine requirements for stasis, and 1-and 2-log reductions of colony-forming units. The results showed that, at least for the E. coli isolates studied, there was a large resistant subpopulation from the inception of infection.…”
Section: Mutational Resistancementioning
confidence: 99%
“…As there is interest in use of parenteral fosfomycin for treatment of indications in addition to uncomplicated UTI, recent hollow fiber pharmacokinetic/pharmacodynamic (PK/PD) studies were undertaken by the Ambrose group (VanScoy et al 2015) to determine the PK/PD index for IV fosfomycin and to determine requirements for stasis, and 1-and 2-log reductions of colony-forming units. The results showed that, at least for the E. coli isolates studied, there was a large resistant subpopulation from the inception of infection.…”
Section: Mutational Resistancementioning
confidence: 99%
“…74,75 Optimal pharmacodynamic targets for fosfomycin are unclear; historically it has been considered a time-dependent agent, but some recent pharmacodynamic studies with fosfomycin against E. coli have shown the fAUC/MIC ratio to be most predictive of efficacy. 76,77 The pharmacodynamics of fosfomycin may differ by species. [76][77][78] The emergence of resistance to fosfomycin has been demonstrated in vitro in studies in both Enterobacteriaceae and Pseudomonas species.…”
Section: Fosfomycinmentioning
confidence: 99%
“…[76][77][78] The emergence of resistance to fosfomycin has been demonstrated in vitro in studies in both Enterobacteriaceae and Pseudomonas species. [76][77][78] This resistance may be suppressed by combining fosfomycin with other agents. [76][77][78][79][80] Though it is generally well tolerated, it should be noted that the intravenous formulation (fosfomycin disodium) contains 330 mg of sodium per gram of fosfomycin, which could be problematic in patients with heart failure.…”
Section: Fosfomycinmentioning
confidence: 99%
See 2 more Smart Citations